Development of a Sustained-Release Oral Tablet of Tyrosine Kinase Inhibitor Imatinib Using Full Factorial Design - Faruk, Omar; Shill, Diponkor Kumar; Hossain, A S M Monjur Al; Rouf, Abu Shara Shamsur; Kumar, Uttom (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Tyrosine kinase inhibitors (TKIs) have dramatically improved the outcomes for patients with leukemia. The conventional immediate-release tablets of imatinib exhibit fluctuating plasma levels. The aim of this study was to develop sustained-release tablets of imatinib to maintain a steadier plasma drug concentration. A 32 fullfactorial design was used for the formulation optimization. The percentages of povidone K30 and methocel K15M were selected as independent variables and drug released after 24h in pH 6.8 phosphate buffer was chosen as a response. Statistical analysis of the response followed by empirical evaluation identified an optimum formulation that involved the use of 1.2% of povidone K30 and 3% of methocel K15M. The optimized formulation released 99.38% of the drug in vitro at pH 6.8 phosphate buffer after 24 hours, with an error of -0.353% to the predicted response and followed first-order release kinetics. The findings of this study enabled us to propose a new imatinib tablet dosage form for a more effective and patient-compliant leukemia therapy. Dhaka Univ. J. Pharm. Sci. 23(2): 135-143, 2024 (December)